Evaluation of the performance of an endoscopic 3-mm electrothermal bipolar vessel sealing device intended for single use after multiple use-and-resterilization cycles - Quitzan, Juliany Gomes [UNESP]; Singh, Ameet; Beaufrere, Hugues; Valverde, Alexander; Lillie, Brandon; Salahshoor, Masoomeh; Bardelcik, Alexander; Saleh, Tarek M. (Wiley-Blackwell, 2020)
Objective To evaluate the performance of an endoscopic 3-mm electrothermal bipolar vessel sealing device (EBVS) intended for single use after multiple use-and-resterilization cycles. Study design Ex vivo study. Sample population Eight 3-mm EBVS handpieces. Methods Handpieces were subjected to a maximum of 15 cycles of testing, including simulated surgery, sealing and burst pressure testing of porcine carotid arteries, reprocessing, and hydrogen peroxide plasma resterilization. Failure was defined as two sequential vascular seal leakage events occurring at <250 mm Hg. Histological evaluation, maximum external temperature of the jaws, sealing time, tissue adherence, jaw surface characterization, and mechanical deterioration were studied. Failure rate was analyzed by using a Kaplan-Meier curve. Linear and ordinal logistic mixed models were used to analyze sealing time, handpiece jaw temperature, and adherence score. Results Mean +/- SD diameter of arteries was 3.22 +/- 0.35 mm. Failure was observed starting at cycle 10 and going up to cycle 13 in 37.5% (3/8) of the handpieces. Tissue adherence increased after each cycle (P < .001). Maximum external temperature (79.8 degrees C +/- 13.9 degrees C) and sealing time (1.8 +/- 0.5 seconds) were not significantly different throughout cycles up to failure. A flatter surface and large scratches were observed microscopically throughout the jaw surface after repeated use and resterilization. Conclusion The 3-mm EBVS handpiece evaluated in this study can be considered safe to use for up to nine reuse-and-resterilization cycles. Clinical significance These data provide the basis for establishing preliminary guidelines for the reuse and hydrogen peroxide plasma resterilization of an endoscopic 3-mm EBVS handpiece.